Conservation Agriculture is Africa : An Analysis of the Role of Social Systems in the Adoption of Conservation Agriculture Technologies in Selected Areas of Zambia and Zimbabwe - Stevens, Joseph Benjamin (University of Pretoria, 2020)
Thesis (PhD (Rural Development))--University of Pretoria, 2020.